Equipment of dry chrysanthemum drink of new forms of energy - LI YANPING; ZHOU XINGYUAN; ZHANG LU; CAI MENGJIAO; ZHANG LIHU; LIU HUI; CAO DANDAN; QIU YUE; HOU TIANTIAN (2018)
The utility model relates to an equipment of dry chrysanthemum drink of new forms of energy, power unit passes through the connection of electric lines in removing the wet -end branch including solarpanel, solar panel, removing wet -end and dividing including the dehumidifier, the dehumidifier is through dehumidification pipe connection in drying box body part, the drying box body part is equipped with sealing door including the box that is multi -layer framework structure, the front side of box, and the right side upper end is equipped with and communicates in the inside air outlet of box, the inside bilateral symmetry of box is equipped with multilayer limiting track, holds the dish and connects inside the box through the plug -type work of limiting track, limiting track's below is equipped with microwave heating equipment and air circulation channel. Its structural design is reasonable, adopts the new forms of energy power supply to replace traditional heating methods, environmental protection and energy s